Solving the problems of studying passenger flow in urban public transport by introducing digital technologies - Aliboev Bakhtiyor; Juraeva Gulchehra; Akhmedov Doniyor; Gulyamov Normakhamat; Abrorov Akbar (E3S Web of Conferences, 2024)
The article presents the results of a study devoted to the analysis of existing problems in determining passenger traffic in urban public transport, as well as the control of passenger traffic and its distribution, in which it is necessary to regularly determine the number of transport structures of bus fleets and conduct analytical monitoring of the flow of passengers in urban public transport. The methods of passenger traffic control and financing in the transport system using digital technologies are proposed.